2017
DOI: 10.1016/j.jad.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of growth curve mixture modelling literature investigating trajectories of perinatal depressive symptoms and associated risk factors

Abstract: Background The aim of this study was to review the growth curve mixture modelling (GCMM) literature investigating trajectories of perinatal maternal depressive symptoms and associated risk factors. Methods A systematic search of peer-reviewed articles published until November 2015 was conducted in seven databases. Articles using GCMM to identify trajectories of perinatal depressive symptoms were considered. Symptoms had to be assessed at least three times, anytime from pregnancy to two years postpartum (PROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 47 publications
11
77
1
Order By: Relevance
“…This study sought to identify latent trajectories of depressive symptoms from pregnancy to 18-month postpartum, and their predictors, among low-income perinatal women in South Africa. Altogether, the four trajectories identified support previous findings using similar modelling techniques [30,33]. First, the chronic low trajectory identified was reported in a previous study conducted in Africa [32], suggesting that, despite the high number and ongoing stressors experienced in LMICs, the majority of women remain at low risk of developing depressive symptoms during the perinatal period.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study sought to identify latent trajectories of depressive symptoms from pregnancy to 18-month postpartum, and their predictors, among low-income perinatal women in South Africa. Altogether, the four trajectories identified support previous findings using similar modelling techniques [30,33]. First, the chronic low trajectory identified was reported in a previous study conducted in Africa [32], suggesting that, despite the high number and ongoing stressors experienced in LMICs, the majority of women remain at low risk of developing depressive symptoms during the perinatal period.…”
Section: Discussionsupporting
confidence: 86%
“…Studies which have used more complex longitudinal analyses, such as growth curve mixture modelling (GCMM), have enabled the identification of latent subgroups of women with both chronic and transient symptom trajectories during the perinatal period, in both HICs [30] and LMICs [31,32]. This allowed investigators to disentangle severity from chronicity and moving away from the dichotomisation of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Any differences identified between trajectories in subsequent phases therefore have a level of uncertainty and do not capture the individual variability within each class. Findings should consequently be interpreted with caution …”
Section: Discussionmentioning
confidence: 99%
“…However, the heterogeneity of levels of depressive symptoms in perinatal mothers and those with young children (under 5 years) has been mentioned in several studies and various social and psychological risk factors have been identified in the trajectory of depressive symptoms (Baron, Bass, Murray, Schneider, & Lund, ; Santos, Tan, & Salomon, ; van der Waerden et al., ). Although the effect of intervention was different for each group, the depressive symptoms of perinatal mothers and those with young children could be explained by complex factors, besides the type and effect of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Young children also affect the mothers if they adapt well to the effect of intervention. In addition, mother-child interaction facilitates interventions (Baron, Bass, Murray, Schneider, & Lund, 2017;Santos, Tan, & Salomon, 2017;van der Waerden et al, 2015). Although the effect of intervention was different for each group, the depressive symptoms of perinatal mothers and those with young children could be explained by complex factors, besides the type and effect of intervention.…”
Section: Discussionmentioning
confidence: 99%